2018
DOI: 10.1002/mnfr.201800057
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Provides Th2 Adjuvant Stimuli and Promotes Sensitization to Egg White Allergens in BALB/c Mice

Abstract: The results obtained reveal that EY provides Th2-adjuvant stimuli to the immune system that may increase the susceptibility to develop egg allergy. The joint administration of EW and EY may be a trigger for initiation or maintenance of egg allergy with implications in prevention strategies regarding egg introduction in the diet of susceptible children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
(80 reference statements)
2
20
0
Order By: Relevance
“…Previous studies, using mouse models of orally induced allergy, indicated that egg yolk provides Th2 adjuvant stimuli to the immune system that may enhance sensitization and susceptibility to develop egg allergy, an aspect also corroborated with other nonrelated food allergens, such as whey proteins [ 7 ]. The investigation of the mechanisms governing polarization towards a Th2 response, concentrating on the early intestinal immune and inflammatory effects in a murine model of acute feeding, showed that egg yolk may promote sensitization to egg white proteins through the activation of innate immune cells, such as intestinal epithelial cells (IECs), dendritic cells (DCs), and group 2 innate lymphoid cells (ILC2s) [ 8 ].…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies, using mouse models of orally induced allergy, indicated that egg yolk provides Th2 adjuvant stimuli to the immune system that may enhance sensitization and susceptibility to develop egg allergy, an aspect also corroborated with other nonrelated food allergens, such as whey proteins [ 7 ]. The investigation of the mechanisms governing polarization towards a Th2 response, concentrating on the early intestinal immune and inflammatory effects in a murine model of acute feeding, showed that egg yolk may promote sensitization to egg white proteins through the activation of innate immune cells, such as intestinal epithelial cells (IECs), dendritic cells (DCs), and group 2 innate lymphoid cells (ILC2s) [ 8 ].…”
Section: Introductionmentioning
confidence: 67%
“…In early life, hyper‐response to boiled egg yolk was found to prolong egg allergy (Horino, Kitazawa, Satou, & Miura, 2019). Moreover, egg yolk could promote egg white sensitization in mice model (Pablos‐Tanarro, Lozano‐Ojalvo, Martínez‐Blanco, Molina, & López‐Fandiño, 2018). Egg yolk and egg white are commonly cooked as a whole, separately, or processed with other food ingredients.…”
Section: Effect Of Processing On Allergenicity Of Eggmentioning
confidence: 99%
“…Samples were stained with the antibodies listed in Table S2, Supporting Information, and live cells were determined with LIVE/DEAD Fixable Near‐IR Dead Cell Stain Kit (Thermo Fisher Scientific). Pablos‐Tanarro et al . was followed for analyses of DCs, and van den Elsen et al.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were stained with the antibodies listed in Table S2, Supporting Information, and live cells were determined with LIVE/DEAD Fixable Near-IR Dead Cell Stain Kit (Thermo Fisher Scientific). Pablos-Tanarro et al [19] was followed for analyses of DCs, and van den Elsen et al [20] and Cortés-Pérez et al [7] for T cell populations. ALDH activity was determined by using ALDEFLUOR staining kit, following the manufacturer's recommendations (Stemcell Technologies Inc).…”
Section: Analyses Of Dendritic and T Cell Subsets And Aldehyde Dehydmentioning
confidence: 99%